Molecular characterization and expression of DERL1 in bovine ovarian follicles and corpora lutea - Lussier Jacques G; Ndiaye Kalidou; Pate Joy L (Reproductive Biology and Endocrinology, 2010)
Abstract The endoplasmic reticulum (ER) is a major site of protein synthesis and facilitates the folding and assembly of newly synthesized proteins. Misfolded proteins are retrotranslocated across the ER membrane and destroyed at the proteasome. DERL1 is an important protein involved in the retrotranslocation and degradation of a subset of misfolded proteins from the ER. We characterized a 2617 bp cDNA from bovine granulosa cells that corresponded to bovine DERL1. Two transcripts of 3 and 2.6 kb were detected by Northern blot analysis, and showed variations in expression among tissues. During follicular development, DERL1 expression was greater in day 5 dominant follicles compared to small follicles, ovulatory follicles, or corpus luteum (CL). Within the CL, DERL1 mRNA expression was intermediate in midcycle, and lowest in late cycle as compared to early in the estrous cycle. Western blot analyses demonstrated the presence of DERL1 in the bovine CL at days 5, 11, and 18 of the estrous cycle. Co-immunoprecipitation using luteal tissues showed that DERL1 interacts with class I MHC but not with VIMP or p97 ATPase. The interaction between DERL1 and MHC I suggests that, in the CL, DERL1 may regulate the integrity of MHC I molecules that are transported to the ER membrane. Furthermore, the greater expression of DERL1 mRNA is associated with the active follicular development and early luteal stages, suggesting a role of DERL1 in tissue remodeling events and maintenance of function in reproductive tissues.